Aromatherapy as a Non-Pharmacological Approach to Pain Management in The Active Phase of The First Stage of Labor - Monica Putri Gustin; Yanti Cahyati; Laila Putri; Meti Widia Lestari; Qanita Wulandara (Green Publisher, 2026)
Birth pain is a physiological condition that can cause stress, anxiety, and tension that result from childbirth, even increasing the risk of complications. This condition can cause severe labor during childbirth, which causes muscular contractions, uteroplacental circulation, vascular circulation, and cervical oxygen, causing uterine ischemia to increase the amount of pain and risk complications during labor. Attempts to reduce the pain of childbirth involve two methods of pain control: pharmacological and non-pharmacological. One attempt to reduce the pain of childbirth by non-pharmacological care could be made by inhaling an aromatic orphanage with a diffuser at the time of childbirth. The study aims to examine the effect of aromatherapy on the intensity of labor pain in the Ciamis flood district in 2025. The study employed a quasi-experimental design with a one-group pretest-posttest approach. The sampling technique used is impressive, employing the Lameshow formula with 45 respondents. The study indicates that there was an average difference in the scale of childbirth pain before and after the lavender aroma was given to mothers in childbirth in the flooded hospital. Thus, aromatherapy can be an effective alternative to non-pharmacological intervention in birth pain management.